Edukasi Mitigasi Dan Rehabilitasi Bencana Guna Mendukung Pembangunan Berkelanjutan Masyarakat Rawan Bencana Di Lampung - Despa, Dikpride; Siregar, Amril Maruf; Ubaidah; Septiana, Trisya; Priyana, Fahrur Riza (FT Universitas Lampung, 2024)
This Community Service Program (PkM) aims to enhance the resilience of the community in facing disasters and to promote the formation of a disaster-resilient society in Padang Cermin, Lampung. The program was implemented using a non-structural disaster mitigation approach through community education and training.The PkM activities were carried out at SMA Negeri 1 Padang Cermin, considering the school's role as a pentahelix element in disaster management, the disaster-prone geographical conditions, and the earthquake incident in May 2022. Disaster mitigation and rehabilitation education and training were provided to the teachers and students of SMA Negeri 1 Padang Cermin, with the hope that they could become education agents and information disseminators to the surrounding community.The training results showed an increase in the knowledge and understanding of the community about disaster management, which is expected to improve their preparedness and resilience in facing disasters. Active participation from the community and positive feedback indicated the successful transfer of technology and information in this program.Overall, this PkM successfully made a positive contribution in enhancing the resilience of the Padang Cermin community against disasters and in realizing a disaster-resilient village